Using narrative reports to support a digital library - Mendonça, E A (Proceedings. AMIA Symposium, 2001)
The vast amount of information collected and stored in clinical systems can be a significant challenge in the integration of digital libraries and electronic medical records, especially the selection of clinical data to be used in the search, retrieval, and summarization processes. In this study, we describe the use of information retrieval measures with natural language processor output to identify critical information in narrative reports. Our hypothesis is that clinical data that occur often in narrative reports are less important to clinicians than findings that occur rarely. We used the information retrieval methods to analyze one year of discharge summaries. We then conducted a performance study, using physicians as subject. Results show that the methods can be used for filtering critical information from reports. Further studies need to be done on evaluation of the method based on an evaluation of the system performance in the context of a digital library